Effect of Front Line Demonstrations on Yield of Field Pea in Ghazipur District of Uttar Pradesh - A.P. Diwedi, V. Diwedi, R.P. Singh,Mamta Singh, D.R. Singh (Indian Journal of Extension Education, 2022)
Field Pea (Pisum sativum L.), also called as pois proteagineux in French,guisante in. Spanish, pisello in Italian, futtererbse in German and matter in Hindi, is an important winter season grain legume crop largely confined to cooler temperate zone. These are two types of cultivated pea i.e. garden pea and field pea. Garden peas areharvested in an immature conditions and cooked as fresh or canned for subsequence uses. Field Pea is generally grown for dry seeds which are used for a variety of snack preparation and dal. The mature pea is highly nutritive containing high proportion of digestive protein (22.5%), carbohydrates ( 62.1 %), fat (1.8%), minerals (calcium, iron) and vitamins (Riboflavin, thiamin etc.). The most probable centre of origin of pea is Mediterranean region of Europe and central Asia.